2009
DOI: 10.1007/s00595-008-3898-0
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured isolated external iliac artery true aneurysm associated with cystic medial necrosis: Report of a case

Abstract: We report a case of a ruptured isolated true external iliac artery aneurysm (EIAA). A 78-year-old woman was admitted to our institution in a shock state after the sudden onset of severe pain in the right hypogastric region. A pulsating mass was found in her right lower abdomen. Computed tomography (CT) with contrast medium showed an isolated EIAA, 40 mm in diameter, with a massive retroperitoneal hematoma. She underwent emergency resection of the aneurysm and reconstruction of the affected artery, without any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…Crivello et al, 15 who first described the case of the isolated EIA aneurysm in association with CMN, reported a higher operative risk owing to the friability of the artery wall caused by the media degeneration. In 2009, Kato et al 16 reported their experiences in the treatment of an EIA aneurysm, but they could not conform the findings of Crivello et al. Similar to the experience of Kato et al, we also did not find fragile vessel walls in our bilateral open aneurysm repair.…”
Section: Discussioncontrasting
confidence: 60%
“…Crivello et al, 15 who first described the case of the isolated EIA aneurysm in association with CMN, reported a higher operative risk owing to the friability of the artery wall caused by the media degeneration. In 2009, Kato et al 16 reported their experiences in the treatment of an EIA aneurysm, but they could not conform the findings of Crivello et al. Similar to the experience of Kato et al, we also did not find fragile vessel walls in our bilateral open aneurysm repair.…”
Section: Discussioncontrasting
confidence: 60%
“…The most common manifestation of the syndrome is aortic dissection, however other locations of the disease were also described [4][5][6][7][8][9][10]. To our knowledge, non-dilated abdominal aortic rupture such as we have observed in a patient treated at our facility was never previously reported and related to the idiopathic CMN.…”
Section: Introductionmentioning
confidence: 85%
“…As the knowledge of the distinct microscopic changes in CMN grew, it became apparent that it might involve different parts of vascular system. Ascending aortic, Valsalva sinus, coronary, iliac and visceral artery aneurysms were all described as manifestations site of CMN [4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…1 They have been described in patients with ages ranging from 27 to 78 years. 2,3 Although most of the reported cases were unilateral, bilateral isolated EIAAs have also been reported. 4 The presentation of isolated EIAA can vary, ranging from asymptomatic to hemorrhagic shock in an emergency.…”
Section: Introductionmentioning
confidence: 99%